Anionic and zwitterionic carboranyl N-heterocyclic carbene Au(i) complexes. Issue 24 (29th February 2016) - Fisher, Steven P.; El-Hellani, Ahmad; Tham, Fook S.; Lavallo, Vincent
Abstract : The syntheses of the first carboranyl N-heterocyclic carbene complexes with transition metals are reported. Abstract : The syntheses of the first carboranyl N-heterocyclic carbene complexes with transition metals are reported. Both unsymmetrical mono-anionic and symmetrical dianionic NHCs readily react with ClAuSMe2 to afford unusual zwitterionic and anionic Au(i ) dimethyl sulfide adducts. The compounds are characterized by NMR, mass spectrometry, and single crystal X-ray diffraction studies. Percent buried volume (% V bur ) calculations indicate that replacement of an adamantyl group by a hydride substituted icosahedral carborane anion results in a 3.7% increase in % V bur .